(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Agricultural communication aims to influence farming and farmers significantly. The most basic definition of communication is the transfer of information from the farmers to the tribal people. By doing that, communication only informs the tribal people of the inclusion of new technology, actual change cannot occur only if the tribal people also obtain the technology and the training necessary to employ it. Schedule areas agriculture is very different from plough farming elsewhere. Generally, tribal communities have low population density, undulating topography, thickly wooded areas, and transportation problems. Most of the hill tribes use shifting farming, in their cultivation. The majority of the hill tribes use shiftfog farming and sometimes prefer alternative cultivation. Tribal people still engage in shifting agriculture due to the physical characteristics of the hills, and unless forced otherwise by physical or economic considerations, they prefer this technique to permanent agriculture. The importance of agriculture communication in schedule areas and coffee cultivation in Araku Valley Andhra Pradesh are covered in the present study.